(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the Frequency of Pancytopenia in children presenting with Malaria Study Design: Descriptive / cross sectional study. Place and Duration of Study: This study was conducted at the Pediatrics Department, DHQ Teaching Hospital, Gomal Medical College, D. I Khan from October, 2015 to April, 2016. Materials and Methods: Before carrying out the research permission was obtained from ethical committee of hospital. Questionnaire was used for collection of data. All children < 18 yrs with malaria were registered in research from OPD. MP and Special smear tests were done for diagnosis of malaria in admitted children with fever. Informed written consent was taken from parents. All the above-mentioned information were recorded in a pre-designed proforma. Strictly exclusion criteria was followed to control confounders and bias in the study results.All the laboratory investigations were done under supervision of single expert pathologist having minimum of five years of experience. Sample size was 232 while technique used was Nonprobability consecutive sampling. Results: In this study males were 60.34% and females were 39.66%. The female to male proportion was 1:1.6.8.51 years+4.23SDwas the average age of the patient. The frequency of pancytopenia among children with malaria was found in 85(36.64%) patients. Conclusion: Pancytopenia is a common problem in clinical practice. The incidence is high in malaria patients. & requires prompt action when patients present with malaria so that one can be managed to decreaseillness and prolong survival.